Anar Phali (Opuntia ficus) juice extract as a novel pollution-free source of natural betalain dye for wool yarn - ÖZOMAY, MERAL (My University, 2023)
Green products such as plant pigments in all filed are gaining fame globally due to their excellent ayurvedic and biological characteristics. In this study, microwave rays have been employed for the isolation of colorants from Anar Phali while bio-mordant have been included to get color-fast shades. The colorant was isolated in an acidic medium before and after microwave rays for 2 min. For getting darker shades with different tints, sustainable chemical and plant-based extracts as bio-mordant have been employed before and after bio coloration of wool yarn at given conditions. CIE Lab system computed in Colori-spectrophotometer (CS-410) was used to observe the change in color depth and tonal variation of dyed fabrics, and ISO standard methods have been employed to rate the colorfastness to light, washing, and rubbing at grey scale. It is concluded that microwave rays have an excellent sustainable efficacy to isolate colorant from Anar Phali powder for wool dyeing, whereas the addition of bio-mordants has made the process more sustainable and eco-friendly.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Mühendislik ve Teknoloji; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Health Sciences; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Yaşam Bilimleri (LIFE); Mühendislik; Farmakoloji ve Toksikoloji; MÜHENDİSLİK, ÇEVRE; TOKSİKOLOJİ; Engineering, Computing & Technology (ENG); Life Sciences (LIFE); ENGINEERING; PHARMACOLOGY & TOXICOLOGY; ENGINEERING, ENVIRONMENTAL; TOXICOLOGY; Çevre Kimyası; Fizik Bilimleri; Kirlilik; Sağlık, Toksikoloji ve Mutajenez; Environmental Chemistry; Physical Sciences; Pollution; Health, Toxicology and Mutagenesis; Betalain; Green extraction; Harmal; Microwave rays; Opuntia ficus; Wool yarn; Betalain; Green extraction; Harmal; Microwave rays; Opuntia fcus; Wool yarn